VD_FINDINFO HC / 2014 / 663 vom 30. Juli 2014 - VD Tribunal cantonal (2014)
ACTION EN PATERNITÉ, EXPERTISE, PÈRE, DROIT D'ÊTRE ENTENDU, MOYEN DE PREUVE | 29 al. 2 Cst., 152 al. 1 CPC (CH), 316 al. 3 CPC (CH)